Development of Farmer Field School methodology for smallholder dairy farmers in Kenya - Minjauw, B.; Muriuki, H.G.; Romney, Dannie L. (Cambridge University Press, 2004)
This chapter focuses on an on-going DFID-funded project in Kenya to adapt and develop the Farmer Field School methodology specifically for livestock, and particularly for smallholder dairy production, focusing on animal health and production issues. On-going project activities are discussed, and an overview is presented of the participatory tools for problem diagnosis, the agro-ecosystem analysis (AESA) exercise, and livestock participatory technology Development.